2018
DOI: 10.1186/s12864-018-4603-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis reveals ncRNA-mediated molecular regulatory network driving secondary hair follicle regression in cashmere goats

Abstract: BackgroundCashmere is a keratinized product derived from the secondary hair follicles (SHFs) of cashmere goat skins. The cashmere fiber stops growing following the transition from the actively proliferating anagen stage to the apoptosis-driven catagen stage. However, little is known regarding the molecular mechanisms responsible for the occurrence of apoptosis in SHFs, especially as pertains to the role of non-coding RNAs (ncRNAs) and their interactions with other molecules. Hair follicle (HF) degeneration is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 54 publications
(51 reference statements)
1
33
0
Order By: Relevance
“…Although there were only three pathways in which the sulfur relay system, sulfur metabolism, and glycosaminoglycan degradation were found to be significantly enriched, the host genes of circRNA6854 and circRNA815 were involved in all pathways. Studies have shown that intermediate filaments are probably the key factors involved in cashmere growth 34 . In addition, several important pathways that play a role in dominating hair follicle development were reported, such as the PPAR pathway 35 , Wnt signaling pathway 5,36,37 , MAPK signaling pathway 38 , and NF-kappa B signaling pathway 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there were only three pathways in which the sulfur relay system, sulfur metabolism, and glycosaminoglycan degradation were found to be significantly enriched, the host genes of circRNA6854 and circRNA815 were involved in all pathways. Studies have shown that intermediate filaments are probably the key factors involved in cashmere growth 34 . In addition, several important pathways that play a role in dominating hair follicle development were reported, such as the PPAR pathway 35 , Wnt signaling pathway 5,36,37 , MAPK signaling pathway 38 , and NF-kappa B signaling pathway 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Xianghui Ma et al found MSI2 , a RNA-binding protein of Musashi, would keep hair follicle resting in process of telogen-to-anagen transition in mice[ 38 ]. In recent study, Guangxian Zhou et al revealed ncRNA might play a regulatory role in skin of cashmere goat through whole transcriptome[ 39 ]. Our study might improve the understanding on the molecular mechanism of the growth cycle of SHF and PHF in Cashmere goats.…”
Section: Discussionmentioning
confidence: 99%
“…The circRNA-1926 is 3887-nt in length, and it exhibited significantly higher level at anagen than the counterpart at telogen [16]. The potential miRNA target sites within circRNA-1926 were predicted and screened through taking intersection of the analysis of three programs: miRDB, RNAhybrid, and miRNA-target, as described in our previous study [1]. We performed the analysis on the nucleotide composition and frequency distribution of nucleotide pairs with MEGA program (Version 6.0) [17].…”
Section: Sequence Analysis Of Circrna-1926mentioning
confidence: 99%
“…Cashmere is precious natural protein fiber derived from cashmere goats, and its textiles have been favored by consumers due to their typical features, like fine, light, softness, and comfort [1,2]. In cashmere goats, the cashmere growth is controlled by biological cycles of secondary hair follicle (SHF) consisting of anagen, catagen, and telogen [3].…”
Section: Introductionmentioning
confidence: 99%